A dança de salão como um dos conteúdos de dança na escola - Volp, Catia Mary [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
This paper presents the right all citizens have to dance. It focus on the official orientations which deals with dance as a legitimate content at school briefly discussing the difficulty to implement this content. Among various dance manifestations we highlight Ballroom Dance, its characteristics and benefits. We trace the historical path of Ballroom Dance in Brazil at colleges.

Este trabalho trata do direito de todo cidadão à dança. Focaliza as orientações oficiais que tratam a dança como conteúdo legítimo na escola discutindo brevemente a dificuldade de efetivação deste conteúdo. Dentre as várias manifestações de dança destaca as Danças de Salão, suas características e benefícios. Traça o percurso histórico da Dança de Salão no Brasil nas instituições de ensino superior.
Ballroom Dance as one of the dance contents at school
Keywords: Ballroom dances; Creative dance; Professional development